How to catch a frog :and other stories about family, love, dysfunction, survival, and DIY / Heather Ross. - Ross, Heather.
Stories of growing up in rural Vermont as part of an eccentric family of artists and idealists, which involved self-imposed poverty, innovative living, daily lessons in self-reliance, and a deep appreciation for the natural beauty of the environment.